Designing the Global City Design Excellence, Competitions and the Remaking of Central Sydney - Freestone, Robert; Davison, Gethin; Hu, Richard (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This text explores how architectural and urban design values have been co-opted by global cities to enhance their economic competitiveness by creating a superior built environment that is not just aesthetically memorable but more productive and sustainable. It focuses on the experience of central Sydney through its policy commitment to 'design excellence' and more particularly to mandatory competitive design processes for major private development. Framed within broader contexts that link it to comparable urban policy and design issues in the Asia-Pacific region and globally, it provides a scholarly but accessible volume that provides a balanced and critical overview of a policy that has changed the design culture, development expectations, public realm and skyline of central Sydney, raising issues surrounding the uneven distribution of benefits and costs, professional practice, representative democracy, and implications of globalization.